Silicon mitigates iron deficiency in two energy cane cultivars by modulating physiological and nutritional mechanisms - Teixeira, Gelza Carliane Marques; Prado, Renato de Mello; Rocha, Antonio Márcio Souza; Princi, Murilo Bassan; Andrade, Caio Soares de (Frontiers in Plant Science, 2023)
Introduction Alkaline soils with iron (Fe) deficiency are found in many regions of the world, and the use of silicon (Si) can mitigate the damages caused by such deficiency. The aim of this study was to evaluate the effect of Si in mitigating a moderate deficiency of Fe in two energy cane cultivars. Methods Two experiments were performed, one with the VX2 cultivar and the other with the VX3 cultivar of energy cane, which were cultivated in pots with sand and a nutrient solution. In both experiments, treatments followed a factorial scheme 2x2, designed based on the sufficiency and deficiency of Fe, being combined with the absence or presence of Si (2.5 mmol L-1), disposed in a randomized blocks design with six replicates. In the condition of Fe sufficiency, plants were cultivated in a solution containing 368 µmol L-1 of Fe, while plants cultivated under deficiency were initially submitted to cultivation with a 54 µmol L-1 concentration of Fe for 30 days, and later, with Fe complete omission for 60 days. The supply of Si was carried out by applying 15 fertirrigations with Si (via root and leaf) during the initial stage of seedling development, and after transplanting, the nutrient solution was added daily (via root). Results and discussion Both cultivars of energy cane were sensitive to Fe deficiency in the absence of Si, impairing its growth by causing stress and pigment degradation, thus reducing the photosynthesis efficiency. The supply of Si mitigated the damages caused by Fe deficiency in both cultivars, by increasing Fe accumulation in new and intermediate leaves, stem, and roots in the VX2 cultivar, and in new, intermediate, and old leaves and stem in the VX3 cultivar, which in turn reduced stress and favored both the nutritional and photosynthesis efficiency, while increasing the dry matter production. Si by modulating physiological and nutritional mechanisms, mitigates Fe deficiency in two energy cane cultivars. It was concluded that Si can be used as a strategy to improve growth and nutrition of energy cane in environments that are susceptible to Fe deficiency.